2020
DOI: 10.1093/ajcn/nqaa141
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting iron and vitamin A status in settings of inflammation: a sensitivity analysis of the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) approach

Abstract: Background Accurate assessment of iron and vitamin A status is needed to inform public health decisions, but most population-level iron and vitamin A biomarkers are independently influenced by inflammation. Objectives We aimed to assess the reproducibility of the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) regression approach to adjust iron [ferritin, soluble transferrin receptor (sTfR)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…The highest infl ammation rates diagnosed by AGP have been reported in Asian and African countries by the BRINDA study. [23] Nonetheless, even though high CRP levels were found only in about 10% of children in the study, some had concentrations much higher than the cut-off point. Chronic infl ammation, assessed by AGP, is associated with a higher frequency of obesity and asthma in children [18] and high CRP values are associated with systemic bacterial infections, tissue damage and allergies.…”
Section: Discussionmentioning
confidence: 66%
“…The highest infl ammation rates diagnosed by AGP have been reported in Asian and African countries by the BRINDA study. [23] Nonetheless, even though high CRP levels were found only in about 10% of children in the study, some had concentrations much higher than the cut-off point. Chronic infl ammation, assessed by AGP, is associated with a higher frequency of obesity and asthma in children [18] and high CRP values are associated with systemic bacterial infections, tissue damage and allergies.…”
Section: Discussionmentioning
confidence: 66%
“…In 2017, researchers from the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project published a new mathematical method to estimate the prevalence of iron and vitamin A in settings of acute and chronic inflammation [ 47 ]. They suggested that without this adjustment, iron deficiency could be under-reported and vitamin A and zinc deficiency could be over-reported [ 47 , 48 , 49 ]. Nevertheless, it is unclear if the results of this study can be used in individuals.…”
Section: Discussionmentioning
confidence: 99%
“…We adjusted PF, RBP and PZn values for inflammation using the regression correction approach proposed by the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) group. This approach accounts for the magnitude of inflammation measured by CRP and AGP, and therefore allows for more precise adjustments of acute phase proteins [ 35 , 36 ]. Iron deficiency (ID) was defined as adjusted PF < 15 µg/L [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…3 Median (inter-quartile range) (all such values). 4 Plasma ferritin adjusted for inflammation [35]. 5 Adjusted plasma ferritin < 15 µg/L [24].…”
Section: Anemiamentioning
confidence: 99%
See 1 more Smart Citation